2021
DOI: 10.20473/mgk.v10i2.2021.278-283
|View full text |Cite
|
Sign up to set email alerts
|

Pendidikan Gizi tentang Anemia dan Konseling Kesehatan Mental pada Remaja melalui Program Kenal Sebaya

Abstract: ABSTRAKLatar belakang: Anemia merupakan suatu kondisi dimana kadar hemoglobin (Hb) di dalam darah lebih rendah dari angka normal. Indonesia merupakan sebuah negara dengan kejadian anemia yang cukup tinggi. Prevalensi kejadian anemia yang terjadi pada Remaja Indonesia yaitu 32%, hal ini memiliki arti 3-4 dari 10 remaja di Indonesia menderita anemia. Program pemberian Tablet Tambah Darah (TTD) adalah salah satu cara yang dapat digunakan sebagai upaya di dalam penanganan anemia. Cakupan pemberian Tablet Tambah Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
1
1
0
4
Order By: Relevance
“…Providing education using leafl et media also shows results in the form of a p-value of <0.001, meaning that there is an eff ect of providing education about anemia and nutrition using leafl et media on the knowledge of young women. The results of this study are in accordance with research conducted by Puspikawati et al (2021) which showed diff erences in anemia knowledge before and after socialization.…”
Section: The Eff Ect Of Leafl Et Education On Anemia and Nutrition On...supporting
confidence: 91%
“…Providing education using leafl et media also shows results in the form of a p-value of <0.001, meaning that there is an eff ect of providing education about anemia and nutrition using leafl et media on the knowledge of young women. The results of this study are in accordance with research conducted by Puspikawati et al (2021) which showed diff erences in anemia knowledge before and after socialization.…”
Section: The Eff Ect Of Leafl Et Education On Anemia and Nutrition On...supporting
confidence: 91%
“…Data yang dikumpulkan mencakup data kadar hemoglobin menggunakan alat EasyTouch PENDAHULUAN Remaja merupakan masa transisi dari masa kanak-kanak menjadi dewasa yang berada pada rentang usia 10-19 tahun (Puspikawati et al 2021). Anemia adalah terjadinya penurunan masa eritrosit yang ditunjukan oleh penurunan kadar hemoglobin, hematrokrit dan eritrosit.…”
Section: Jenis Dan Cara Pengumpulan Dataunclassified
“…Various kinds of media can be used to provide education or knowledge to clients or families about anemia and Blood Supplement Tablets. Education about anemia and blood-supplementing tablets in adolescents using video media and online leaflets can increase adolescents' knowledge about anemia and blood-supplementing tablets (Puspikawati, et al, 2021).…”
Section: Analysis Of the Implementation Of Monitoring And Education I...mentioning
confidence: 99%